Pengembangan Obyek Daya Tarik Wisata Kembang Soka di Perbukitan Menoreh, Kulon Progo, Yogyakarta - Pramudya, Wisnu; Fauzia, Shifa; Rahayu, Nurul Asri; Sukma, Tiara (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
Kembang Soka, in the Menoreh Hills of Yogyakarta, is a nature-based tourist attraction with distinctive landscape such as waterfalls and turquoise pools. Earlier studies emphasized managerial strategies, while the site’s intrinsic identity received little attention. This study identifies the “energy” of Kembang Soka through four aspects (originality, authenticity, uniqueness, and beauty) and formulates branding and a development concept rooted in these values. A descriptive qualitative method was applied through field observation, literature review, and interviews with local community and tourists. Findings show that originality is tied to folklore, particularly the legend of Prince Diponegoro and the Tuk Jaran spring, and natural phenomena such as dual-colored waters and rich biodiversity. Authenticity emerges from the convergence of three waterfalls, seven springs, and the geological formations of Jonggrangan and Kaligesing. Uniqueness is reflected in wooden bridges, natural dams, and the interplay of water and rock colors that create distinctive landscapes. Beauty is experienced visually, psychologically, climatically, and socially, reinforced by the hospitality of local people. Based on these energies, the study proposes branding with the tagline “Feel, Breath, and Jump!” and a development concept called Natural Spring. The research contributes theoretically to energy-based destination development and practically to sustainable development and branding strategies.